Capital, Conversion, and Settler Colonialism in Samuel Butler's Erewhon. (28th May 2020) - Fermanis, Porscha
Abstract: Viewing capitalism as emerging primarily from within the framework of empire rather than the nation state, this essay considers the relationship between capital, conversion, and settler colonialism in Samuel Butler's Erewhon, or Over the Range (1872). It looks, first, at the novel's critique of Wakefieldian organized settlement schemes as systems sustained by various forms of capital accumulation and free/unfree labour; and second, at its over-arching evangelical conversion narrative, which both frames and structures the main body of the text. The essay argues that, far from directing its satire wholly or even primarily towards metropolitan Britain, the novel enacts two circulating mid-nineteenth-century settler colonial anxieties: concerns about a perceived crisis of diminishing industriousness and economic exhaustion in colonial Australia and New Zealand, and concerns about the efficacy of British humanitarianism and missionary conversion. It considers the former in the context of the disruptions to settlement caused by the gold rushes in Australia and New Zealand in the 1850s and 1860s, and the latter in the context of missionary and humanitarian efforts to ameliorate conditions for Indigenous peoples from the 1830s onwards. The essay's larger claim is that Erewhon presents capital and conversion as structurally interconnected mechanisms of an evolving Anglo-settler state in New Zealand. Radicalizing a tradition of economic critique of empire beginning with Adam Smith, Butler satirizes the idea of colonialism as an essentially liberal system by showing how much it is intertwined with exploitative practices of territorial expansion, dispossession, capital accumulation, unfree labour, missionary conversion, and racial assimilation.